Accuracy Assessment of Duhok City Land use Official Maps - Raad Awad Kattan; Farsat H. Abdulrahman (Polytechnic)
In this study, the geometric accuracy of four different maps for three sectors of Duhok city was assessed. The maps were produced in different periods and different techniques. One set of maps was paper plotted maps, which had to be geo-referenced. The other three maps were digitally plotted with reference to the global coordinate system UTM/WGS-84/Zone 38 N projection. A total of 51 points were identified on one reference map, which is the master plan of Duhok city prepared by the general directorate of urban planning/Kurdistan region/Iraq with the collaboration of the German company Ingenieurburo Vossing Company. The reference map, which is the master plan of Duhok governorate, is an official map that is certified and checked by the ministry of planning of the Kurdistan region to have a positional accuracy of ±1.5 cm. These points were searched for and identified on the other three maps. Discrepancies in Easting and Northings of these points were calculated, which resulted in the mean discrepancy of 2.29 m with a maximum value of 8.5 m in one event. The maximum standard deviation in dE and dN was 3.8 m. These values are reasonably accepted, considering that the maps were prepared using different techniques and a variable accuracy standard.